Clinical, radiological, therapeutic and prognostic differences between MOG-seropositive and MOG-seronegative pediatric acute disseminated encephalomyelitis patients: a retrospective cohort study - Dong, Xueshan; Jiang, Yan; Yuan, Ping; Fan, Xiao; Ma, Jiannan; Wu, Peng; Jiang, Li; Li, Xiujuan (Frontiers in Neuroscience, 2023)
Objective This study aimed to compare the clinical, radiological, therapeutic, and prognostic differences between pediatric patients showing acute disseminated encephalomyelitis (ADEM) with and without myelin oligodendrocyte glycoprotein (MOG) antibodies. Methods We retrospectively collected all available data of children diagnosed with ADEM and tested for serum MOG antibodies at the Children's Hospital of Chongqing Medical University from January 2017 to May 2021. Results A total of 62 patients were included in our cohort, of which 35 were MOG-seropositive and 27 were MOG-seronegative. MOG-seropositive ADEM children presented with significantly lower rates of seizures (P = 0.038) and cranial nerve (III–XII) palsy (P = 0.003). Isolated leukocytosis in the blood was more common in ADEM children with MOG antibodies (P < 0.001). The two groups showed no significant differences in the distributions and extent of the MRI lesions as well as the appearance of typical/atypical magnetic resonance imaging (MRI) features. MOG-seropositive children were more likely to relapse (P = 0.017) despite having slower oral prednisolone tapering after acute treatments (P = 0.028). In scoring performed on the basis of two neurological function scoring systems, MOG-seropositive children showed milder neurological disability status at onset (P = 0.017 and 0.025, respectively) but showed no difference during follow-up. Conclusion In summary, the differences in the clinical manifestations and auxiliary examination findings for MOG-seropositive and MOG-seronegative ADEM children lacked significance and specificity, making early identification difficult. MOG-seropositive children were more likely to relapse and showed slower steroid tapering. Moreover, MOG-seronegative children tended to have more severe neurological impairments at onset with no difference during follow-up.